La multiplicité des échelles dans l’analyse d’un phénomène d’interface nature/société. L’exemple des feux de brousse en Afrique de l’ouest - Hélène Dolidon (Cybergeo, 2007)
Bushfires constitute a particularly complex phenomenon, because they are situated at the nature/society interface. The objective of this article is to show the consequences of these peculiarities as regards scale and analysis.A first part reviews connections between space and time in the analysis of the bushfires distribution. A definition of "the space of fires" is proposed. In the second part, we consider some of the combinations of the fires distribution factors at several spatiotemporal scales: the global, regional and local scale. Every scale brings a new set of problems which coincides with a new nature/society interface. In a third part, we study the crossing of observation scales. Indeed, the phenomenon’s complexity does not lie only in its many components and their interactions but also in the overlapping of several scales. It results that bushfires are a good example for showing the opposition between the scale or the temporality of the biophysical process and the scale or temporality of its effect.The usual models of observation used in each discipline are insufficient to analyze the phenomenon of the bushfires in its complexity. The study of this phenomenon makes it necessary to take into account several space-time scales, to classify the factors according to scales of observation and to analyze the spatiotemporal interferences between natural factors and anthropic factors.